PENDIDIKAN ISLAM DALAM KONSTELASI ERA GLOBAL: STUDI KASUS DI MTS YAPIKA TANJUNGSARI PETANAHAN KEBUMEN - M Slamet Yahya (Jurnal Penelitian Agama, 2019)
The results of this study are first, the development of vision and mission adapted to the development of science and technology while continuing to prioritize Islamic values; second, curriculum development becomes a multi triple curriculum (Ministry of Religion curriculum, Ministry of National Education curriculum, and Islamic boarding school curriculum); third, the development of learning activities which include; night-time activities, tahfidz activities, tahsin activities, language development, religious moral formation, development of local and global insightful education; fourth, the development of community service in the form of village collaboration participation, care of janazah, distribution of zakat fitrah, distribution of zakat mal, and distribution of qurban animals; fifth, the development of madrasa governance internally between students, teachers, principals, and education personnel, externally between schools and foundations and school committees; sixth, developing networking with parents of students, alumni, government agencies, universities, and other agencies, seventh; MTS YAPIKA is an integrated madrasa, the madrasa students besides getting formal education, they also get pesantren education or are said to be MTS YAPIKA students and al-Istiqomah Islamic boarding school students. Keywords: Madrasa, Islamic Boarding Schools, and Globalization.